The diagnosis of Adamantiades-Behçet disease: Clinical features and diagnostic/classification criteria - Bergamo, Serena (Frontiers in Medicine, 2022)
Adamantiades-Behçet’s disease (ABD) is a chronic-relapsing multisystemic inflammatory disease with unknown etiology first described by a Greek ophthalmology Benediktos Adamantiades and a Turkish dermatology Hulusi Behçet. Any organ or apparatus may be involved, though more often there is an involvement of oral and genital mucosae as well as ocular lesions, skin features, and vascular findings. Since there is neither laboratory nor radiological pathognomonic test, the diagnosis is basically clinical according to peculiar signs and symptoms of the disease. With the purpose of giving objectivity and homogeneity to the diagnosis, many authors in time introduced a long series of diagnostic and classification criteria for Adamantiades-Behçet’s disease. This mini-review provides an overview of published diagnostic/classification criteria.